2013
DOI: 10.1515/jpm-2012-0259
|View full text |Cite
|
Sign up to set email alerts
|

Improving admission temperature in extremely low birth weight infants: a hospital-based multi-intervention quality improvement project

Abstract: A concerted QI approach improved admission temperature in ELBW neonates, with more neonates in the euthermic range, without increasing the risk for hyperthermia. Such an approach could be associated with improved outcomes in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 0 publications
0
58
1
6
Order By: Relevance
“…11 Strategies introduced to minimize heat loss include occlusive wrapping, exothermic warming mattresses, warmed humidified resuscitation gases, polyethylene caps, and higher delivery room (DR) temperatures. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Despite these interventions, hypothermia still occurs in a substantial number (10%-35%) of infants. 18,24,26 Additionally, hyperthermia (temperature .37.5°C) is also more common and presumed to be related to the more aggressive rewarming efforts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Strategies introduced to minimize heat loss include occlusive wrapping, exothermic warming mattresses, warmed humidified resuscitation gases, polyethylene caps, and higher delivery room (DR) temperatures. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Despite these interventions, hypothermia still occurs in a substantial number (10%-35%) of infants. 18,24,26 Additionally, hyperthermia (temperature .37.5°C) is also more common and presumed to be related to the more aggressive rewarming efforts.…”
Section: Discussionmentioning
confidence: 99%
“…33 Investigators have evaluated different interventions, predominantly in VLBW infants ,1500 g or a GA ,30 weeks, to prevent heat loss, including using occlusive wrap, exothermic mattresses, warm caps, polyethylene caps, or heated humidified air or raising the OR temperature either singularly or in combination, with varied success. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Because of baseline data demonstrating frequent hypothermia in the larger premature infant, the combination approach of wrap, exothermic mattress, and cap was extended to all infants ,35 weeks old. Indeed, the greatest impact of the QI was noted in these infants.…”
Section: Discussionmentioning
confidence: 99%
“…Various combinations of these strategies may be reasonable to prevent hypothermia in infants born at less than 32 weeks of gestation (Class IIb, LOE B-R, B-NR, C-LD). Compared with plastic wrap and radiant warmer, the addition of a thermal mattress, [66][67][68][69][70] warmed humidified gases, 71,72 and increased room temperature plus cap plus thermal mattress 55,57,59,73 were all effective in reducing hypothermia. For all the studies, hyperthermia was a concern, but harm was not shown.…”
Section: Nrp 599mentioning
confidence: 99%
“…42,43,48,66 One small randomized clinical trial 78 (very-low-quality evidence, downgraded for indirectness and serious imprecision) showed a reduction in adverse events, including death, intracranial hemorrhage, necrotizing enterocolitis, and oxygen dependence with improved temperature management, but 3 randomized controlled trials [79][80][81] (low-quality evidence, downgraded for indirectness and imprecision) did not show any significant improvement in mortality with significantly improved temperature control. Four observational studies 60,61,63,82 (very-low-quality evidence, downgraded for indirectness and imprecision) did not find any improvement in mortality with improved admission temperatures, but they were not sufficiently powered for this outcome.…”
Section: Consensus On Sciencementioning
confidence: 99%